PERANCANGAN PERPUSTAKAAN UMUM KOTA MALANG DENGAN GAYA MID CENTURY MODERN - syahputri, leonie aaliyah; Indarto (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2024)
Public libraries play an important role with a functional approach, namely the library as a container that can be a source of information in terms of improving intellectual abilities and literacy abilities.The enthusiasm of the Malang city people who come to visit the Malang city public library is very high to provide quality human resources. The community's mastery of literacy is very important. The Malang City public library design method is based on field studies or literature studies as basic materials through a design process which includes three stages, namely input, analysis and output. Designing a public library with a Mid Century Modern style will be able to create an appearance that is more modern, functional, and conducive to the desired atmosphere and goals by using ergonomic and anthropometric approaches which will later standardize the size and shape of the interior.